Catchment to coast contaminant transport to a protected marine park on the East coast of Australia - Melanie Taylor; Daniel Matthews; Benjamin Mos; Symon Dworjanyn; Christian J. Sanders (Environmental Science and Pollution Research, 2026)

Range expansion of a widespread Indo‐Pacific haemulid, the barred javelin Pomadasys kaakan (Cuvier, 1830), in a climate change hotspot - Benjamin Mos; Daniel Mos (Journal of Fish Biology, 2022)
The authors report a first sighting of a euryhaline fish in the climate change hotspot along Australia's south‐eastern coast. The barred javelin, Pomadasys kaakan (Cuvier, 1830) was found in the Nambucca River in New South Wales, Australia, during 2021 and 2022. Specimens were adult, suggesting they may not be transitory vagrants. The new southernmost location recorded here represents a c. 200 km out‐of‐range sighting compared to previous records, and is c. 380 km south of the southernmost Australian stronghold of the species in Moreton Bay, Queensland.